Graphene ink for 3D extrusion micro printing of chemo-resistive sensing devices for volatile organic compound detection. Issue 10 (4th March 2021) - Hassan, Kamrul; Tung, Tran Thanh; Stanley, Nathan; Yap, Pei Lay; Farivar, Farzaneh; Rastin, Hadi; Nine, Md Julker; Losic, Dusan
Abstract : Printed electronic sensors offer a breakthrough in the availability of low-cost devices for improving the quality of human life. Conductive ink is the core of printing technology and is one of the fastest growing ink industries. Abstract : Printed electronic sensors offer a breakthrough in the availability of low-cost sensor devices for improving the quality of human life. Conductive ink is the core of printing technology and also one of the fastest growing sector among all ink industries. Among many developed conductive inks, graphene-based inks are especially recognized as very promising for future fabrication of devices due to their low cost, unique properties, and compatibility with various platforms such as plastics, textiles, and paper. The development of graphene ink formulations for achieving high conductivity and high resolution printing is highly realized in 2D inkjet printing. Unfortunately, the ongoing development of graphene inks is possibly hampered by the non-uniform particle size and structures ( e.g., different shapes and number of layers), which adversely affect printing resolution, conductivity, adhesion, and structural integrity. This study presents an environmentally sustainable route to produce graphene inks specifically designed for 3D extrusion-printing. The application of the prepared ink is demonstrated by mask-free automatic patterning of sensing devices for the detection of volatile organic compounds (VOCs). The sensing devices fabricated with this new ink display high-resolution patterning (average height/thickness of ∼12 μm) and a 10-fold improvement in the surface area/volume (SA/V) ratio compared to a conventional drop casting method. The extrusion printed sensors show enhanced sensing characteristics in terms of sensitivity and selectivity towards trace amount of VOC ( e.g. 5 ppm ethanol) at room temperature (20 °C), which highlights that our method has highly promising potential in graphene printing technology for sensing applications.